2002
DOI: 10.2981/wlb.2002.004
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation in annual survival probability of the Eurasian woodcock Scolopax rusticola wintering in France

Abstract: The Eurasian woodcock Scolopax rusticola is an important quarry species hunt ed all over its range. Some authors have reported local declines in both winter ing and breeding woodcock numbers. In order to investigate whether these pos sible declines are the result of a negative trend in survival, we analysed 3,312 recoveries of 15,839 woodcocks ringed in France during 14 consecutive win ters (1984/85-1997/98). We distinguished between winter (October& n d a s h ; February) and summer (March& n d a s h ; Septemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 19 publications
3
44
3
Order By: Relevance
“…The winter survival rate found in our study (0.55, n = 51) was lower than that reported for France for both adults and firstwinter birds (0.77 and 0.59, respectively; Tavecchia et al 2002), and also lower than the annual survival rate reported for adults in the UK (0.58; Hoodless and Coulson 1994). It was only higher than that reported for first-winter birds in the UK (0.47; Hoodless and Coulson 1994).…”
Section: Winter Survival Ratecontrasting
confidence: 55%
See 4 more Smart Citations
“…The winter survival rate found in our study (0.55, n = 51) was lower than that reported for France for both adults and firstwinter birds (0.77 and 0.59, respectively; Tavecchia et al 2002), and also lower than the annual survival rate reported for adults in the UK (0.58; Hoodless and Coulson 1994). It was only higher than that reported for first-winter birds in the UK (0.47; Hoodless and Coulson 1994).…”
Section: Winter Survival Ratecontrasting
confidence: 55%
“…These studies also suggest that hunting is an additive mortality factor, because annual survival rates for woodcock wintering in areas without hunting (Duriez et al 2005b, Aradis et al 2008) was higher than annual survival rate for woodcock in areas with hunting activity (Hoodless and Coulson 1994, Tavecchia et al 2002, Bauthian et al 2006; see also Bruggink et al 2013 for American Woodcock). According to that, and given that woodcock winter survival rates in this study varied in relation to hunting opportunity, this may indicate source-sink population dynamics among areas with different hunting pressure, as described in France (Péron et al 2011b and.…”
Section: Winter Survival Ratementioning
confidence: 99%
See 3 more Smart Citations